Biocarbon from bark or black pellets as an alternative for coal in steelmaking – techno-economic evaluation. Issue 8 (16th November 2020) - Hakala, Juha; Kangas, Petteri; Rintala, Lotta; Fabritius, Timo; Koukkari, Pertti
ABSTRACT: In 2018, global crude steel production was approx. 1.8 gigatonnes while its direct CO2 emissions stood at 2 giga tonnes (2017), representing 23.5% of all direct industrial emissions. Globally iron and steel industry (ISI sector) is the second largest emitter after the cement industry while in Finland and Sweden the ISI sector is the largest industrial source of fossil CO2 . Biocarbon received from forest sector residues, such as bark, sawdust and lignin, provides an opportunity to a rapid reduction in fossil CO2 emissions in the industry. Use of biocarbon for reduction purposes bestows an asset for both the forest and metals production and processing industry in Finland as well as in the Scandinavian countries. In this study, the focus was on the techno-economic evaluation of biocarbon production (1) from bark-based black pellets produced in a stand-alone plant close to a steel mill and (2) from bark produced in a pulp mill integrated plant. The economics of biocarbon production costs from bark appear promising, providing also an ample source, at an annual potential of up to 95, 000 tonnes of biocarbon from a single pulp mill. GRAPHICAL ABSTRACT: